SOCIAL STATUS OF ATHLETES WITH SPECIAL NEEDS (Heritage, 2022)
The latent structure of manifest status characteristics has been analyzed on different samples from the Serbian population described by different sets of status variables by means of different methods for analyzing latent structures in several studies conducted in different periods of social, political and economic development. Accordingly, the results obtained from the analyses have been different; however, there have regularly appeared some stable latent structures, such as parents’ educational and professional status, respondent’s educational and professional status, as well as family’s socio-political engagement, residence status and economic status.For the past time, great social, economic and political changes have taken place. These changes have inevitably had some impact on both the configuration of status characteristics and the number and nature of latent status dimensions. This study will present the results obtained during this period of the country’s social, political and economic development, in which a representative set of status characteristics describes a representative sports sample from the Serbian population.
Keywords: structure, characteristics, social status, factor, sport, segment